Catholic School Principal Job Satisfaction: Keys to Retention and Recruitment - Fraser, Jennifer; Brock, Barbara L. (Catholic Education: A Journal of Inquiry and Practice, 2006)
This article presents a study on principal retention in New South Wales, Australia. Factors in job retention included economic security, role enjoyment, and the opportunity to contribute. Disincentives to the principalship included lack of support from the employing authority, inadequate pay, isolation, growing responsibilities, difficult parents, and interfering pastors. Findings suggested that the ideal principal role would include greater remuneration, a more supportive employing authority, clearly defined role expectations, and job recognition.